PENGARUH PENGGUNAAN MEDIA STIK TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS II MATERI PENJUMLAHAN DAN PENGURANGAN UPTD SDN TANJUNG JATI 2 KAMAL - Ilmiyah; Nilamsari Damayanti Fajrin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to determine whether there is an effect of using stick media on the learning outcomes of second-grade students. The type of research conducted is a pre-experimental design with a one-group pretest-posttest design. The population of this study is all second-grade students at SDN Tanjung Jati 2 Kamal. The sampling technique used a saturated sample, meaning the entire population was used as the sample, so in this study the sample consisted of 12 students. Research data were collected using test sheets, observation sheets for the implementation of learning activities, and questionnaires on students' responses to the use of stick media.he research results show that the average student ability on the pretest was 57.50 and on the posttest was 77.50. The hypothesis test using an independent sample t-test from the treatment results obtained a significance value of 0.006 < 0.05 and tcount > ttable, which is 3.388 > 2.010. Based on these results, Ho is rejected and Ha is accepted, meaning that there is an effect of stick media on the mathematics learning outcomes of second-grade students on addition and subtraction at UPTD SDN Tanjung Jati 2 Kamal.